Histopathologic Characterization and Neurodegenerative Markers in Patients With Limbic Encephalitis Undergoing Epilepsy Surgery - Rácz, Attila; Hummel, Chiara A.; Becker, Albert; Helmstaedter, Christoph; Schuch, Fabiane; Baumgartner, Tobias; von Wrede, Randi; Borger, Valeri; Solymosi, László; Surges, Rainer; Elger, Christian E. (Frontiers in Neurology, 2022)
Purpose Limbic encephalitis is an increasingly recognized cause of medial temporal lobe epilepsy (mTLE) and associated cognitive deficits, potentially resulting in hippocampal sclerosis (HS). For several reasons, these patients usually do not undergo epilepsy surgery. Thus, histopathologic examinations in surgical specimens of clearly diagnosed limbic encephalitis are scarce. The purpose of this study was a detailed histopathologic analysis of surgical tissue alterations, including neurodegenerative markers, in patients with limbic encephalitis undergoing epilepsy surgery. Methods We investigated the surgical specimens of six patients operated on with mTLE related to limbic encephalitis (among them four patients were with GAD65 and one with Ma1/2 antibodies), and compared the findings to a control group with six patients matched according to age at the time of surgery without limbic encephalitis and without early inciting events. Results Histopathologic analysis in the group with limbic encephalitis revealed HS in four patients, while three of them also displayed signs of an active inflammatory reaction with lymphocytes. In one of the patients with GAD65-encephalitis who was suffering from a late-onset mTLE and a long disease course, neurodegenerative protein markers (β-amyloid and hyperphosphorylated tau) were found coexisting with inflammatory reactions and HS. Investigations in the control group did not reveal any inflammatory reaction or neurodegenerative marker. Conclusion Our findings suggest a possible link between long-lasting immune reactions in the medial temporal lobe, HS, and further toward the development of neurodegenerative diseases. Presently, however, a causal relationship between these entities cannot yet be established. Furthermore, our results suggest that an immunological etiology should always be considered in late onset (> 18 years) mTLE, also in cases of long disease duration and the presence of HS.